Verification of the rule of thumb to determine electron range parameter using egsnrc Monte Carlo - Aisa, Nur Iffah Husna (Universiti Sains Malaysia, 2025)
This study successfully models and validates the Varian Clinac iX linear accelerator for 9 MeV and 12 MeV electron beams using the EGSnrc Monte Carlo simulation framework, specifically BEAMnrc and DOSXYZnrc. The LINAC head was accurately reconstructed using nine component modules (CMs), representing key structures such as the primary collimator, scattering foils, and applicator, with material properties defined through the 700icru.pegsdat file for precise particle interaction modelling. A phase space file generated at 100 cm SSD was used to simulate dose distribution in a voxelised water phantom that replicates clinical setups. Experimental data, collected with a Markus plane-parallel ionisation chamber following IAEA TRS-398 protocol, served to validate the MC-generated PDD and beam profiles. The simulation showed strong agreement with measured values, with percentage differences for R₁₀₀, R₉₀, R₅₀, and Rp within clinically acceptable limits. Beam flatness and symmetry also aligned closely with measurements, aside from slight discrepancies at 12 MeV due to potential geometric modelling issues. Additionally, comparison with rule-of-thumb estimates for electron range parameters confirmed the accuracy of the simulation. Overall, the study demonstrates that EGSnrc, when combined with precise input data and geometric modelling, can produce high-fidelity dose predictions suitable for clinical treatment planning, quality assurance, and benchmarking in electron beam therapy.